2020
DOI: 10.18006/2020.8(spl-1-sars-cov-2).s158.s175
|View full text |Cite
|
Sign up to set email alerts
|

Current Scenario of the Pandemic Covid-19: An Overview

Abstract: The novel coronavirus disease-19 (COVID-19) caused by the SARS-CoV-2 is an emerging disease with deadly consequences, extended its stride over the globe commenced from the epicenter, Wuhan wet market, China led to declare globally as pandemic disease. Several non-specific features of the disease like prolonged incubation period, asymptomatic yet contagious, longer illness duration, and conveyance post clinical recovery feature makes prevention difficult and is the key reason for its rapid spread across the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In 2002–2003, SARS-CoV-1 (unknown then) caused a serious epidemic of severe pulmonary disorder in human populations which spread to four continents [ 30 ]. 8096 persons got infected and it claimed life of 774 victims, creating a 10% mortality rate [ 31 ]. On epidemiological surveillance of the disease it was demonstrated that this novel coronavirus originated from bats, spread to raccoon dogs, Chinese ferret badgers and Himalayan palm civets at Guangdong wet markets, China [ 32 ].…”
Section: Biological Role and Health Disorders Caused By Coronavirusesmentioning
confidence: 99%
“…In 2002–2003, SARS-CoV-1 (unknown then) caused a serious epidemic of severe pulmonary disorder in human populations which spread to four continents [ 30 ]. 8096 persons got infected and it claimed life of 774 victims, creating a 10% mortality rate [ 31 ]. On epidemiological surveillance of the disease it was demonstrated that this novel coronavirus originated from bats, spread to raccoon dogs, Chinese ferret badgers and Himalayan palm civets at Guangdong wet markets, China [ 32 ].…”
Section: Biological Role and Health Disorders Caused By Coronavirusesmentioning
confidence: 99%